Sanctions for the Criminal Act of Extramarital Abortion Based on Article 346 of the Indonesian Criminal Code and Islamic Criminal Law - Wanda Fitri Rahayu; Ali Khosim; Riyan Ramdani (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The criminal act of abortion constitutes a form of crime that threatens human life and frequently occurs in society, especially as a result of promiscuity among unmarried teenagers. Abortion has become a legal issue regulated in Article 346 of the Criminal Code. However, there are limited exceptions in Law Number 36 of 2009 on Health which permits abortion in medical emergencies and pregnancies resulting from rape. The purpose of this study is to explain abortion as an impact of promiscuity, economic factors, and socio-cultural factors. In addition, to gain an understanding of the positive legal regulations in Indonesia regarding sanction of abortion as regulated in Article 346 of the Criminal Code, and to examine the perspective of Islamic law in viewing the practice of abortion and their sanctions. The approach of legal relativism and criminalization is used to understand the complexity of the abortion phenomenon, demonstrating the need for harmonization between criminal law and reproductive health so that law enforcement is humane and in accordance with applicable social norms. The method used in this study is a normative juridical approach using a literature study technique. The research findings reveal that the practice of abortion among adolescents occurs due to weak social control, promiscuity, as well as economic factors, open access to pornographic content, and minimal supervision of people who encourage pregnancy outside of marriage. From a positive legal perspective, abortion regulations in Indonesia are still inconsistent. The Criminal Code criminalizes abortion without medical reasons, especially in Article 346, while in Law Number 36 of 2009 provides exceptions in cases of medical emergencies or rape. From the perspective of Islamic criminal law, this study found that abortion is viewed as a forbidden act, especially if it is performed after the fourth month of pregnancy, when it is believed that the spirit has been blown.